(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article contains an analysis of non-traditional forms existing in Russia and the world employment of the population. The author studied such non-traditional forms of employment as home work and self-employment, agency work, staff leasing, outstaffing, outsourcing services, telework, freelance. The article briefly outlines the differences between non-traditional forms of employment and traditional ones; the advantages and disadvantages of the use of non-traditional forms of employment for employees, employers and society as a whole are systematized. Made by the author the conclusion is that non-traditional forms of employment will develop further, since they allow not only to reduce staff costs, balance the work and personal life of workers, but also increase the actual age of those employed in the country, which is especially important in the face of labor shortages and unfavorable pension trends. In conclusion, the author concludes that the prohibition of non-traditional forms of employment is unproductive and proposes to study in detail the impact of such forms of employment on the development of the country’s economy